Reviving the classical Islamic architectural designs of mosque in tin mining area: Kinta Valley, Perak, Malaysia / Wan Noor Anira Hj Wan Ali @ Yaacob ... [et al.] (2015)
Mosques are physical symbols of centres for religious worship for Muslims all over the world. Besides, mosques are places of worship for the Muslim communities are the most important physical elements for the Muslim community ever since the era of the Prophet Muhammad (peace be upon him) right until now. In Perak State there are some of the mosques which are more than 100 years old and have a symbol of the Classical Islamic architecture which had been influenced by foreign cultures. Thus, this study will identify the history of foreign cultural influence of the mosques in tin mining area and to conserve and preserve the architectural designs of mosques in the Kinta Valley, Perak, Malaysia. The study identified that the mosques in the Kinta Valley have been influenced by foreign cultural. Moreover, the findings of this study can also be used to educate the public of the importance of the value of our architectural heritage and help to preserve our local cultural heritage.